The Impact of Marketing on The Business Performance of Companies: A Literature Review; Pazarlamanın Şirketlerin İş Performansı Üzerindeki Etkisi: Bir Literatür Taraması - A. Selçuk Köylüoğlu; Petek Tosun; Mesut Doğan (Journal of Social Sciences of Muş Alparslan University, 2021)
The technology-based global competition environment that pushes businesses to constructive transformation in order to ensure customer satisfaction has further increased the importance of marketing capabilities in business strategies. The purpose of the literature review is to summarize the previous studies about marketing-financial performance nexus. Studies that were published between 1969 and 2019 could be reached from the EBSCO database were included in the literature review. A significant number of studies conducted in different countries have shown that marketing spending is an investment that creates value for the company and has a positive impact on firm profitability, firm value or firm sales. This study contributes to the literature by summarizing the research findings on the effects of marketing investments on business performance. – – Müşteri memnuniyetini sağlamak için işletmeleri konstrüktif transformasyona iten teknoloji tabanlı küresel rekabet ortamı, pazarlama yeteneklerinin işletme stratejilerindeki önemini daha da artırmıştır. Bu çıkış noktasından hareketle kurgulanan literatür incelemesinin amacı, pazarlamafinansal performans ilişkisine ait daha önceki çalışmaları özetlemektir. Literatür taramasına 1969- 2019 yılları arasında yayımlanan ve EBSCO veri tabanından ulaşılabilen çalışmalar dahil edilmiştir. Farklı ülkelerde yapılan önemli sayıda araştırma, pazarlama harcamalarının şirket için değer yaratan ve firma kârlılığı, firma değeri ya da firma satışları üzerinde olumlu etkisi olan bir yatırım olduğunu göstermiştir. Önemli bir konuya odaklanan bu çalışma, pazarlama yatırımlarının işletme performansı üzerindeki etkilerine ilişkin araştırma bulgularını özetleyerek, literatüre katkıda bulunmaktadır.
Keywords: 330; Marketing; Marketing Instruments; Business Performance; Financial Performance